Young children and tablets: A systematic review of effects on learning and development - Herodotou, C. (Journal of computer assisted learning, 2018)
Mobile applications are popular among young children, yet there is a dearth of studies examining their impact on learning and development. A systematic review identified 19 studies reporting learning effects on children 2 to 5 years old. The number of children participating in experimental, quasi‐experimental, or mixed‐method studies was 862 and in descriptive or correlation studies, 941. The majority of studies reported positive effects on literacy development, mathematics, science, problem‐solving, and self‐efficacy. Among the factors explaining observed effects were design features, the role of adults, and a similarity between applications and transfer context. Although drawing firm conclusions remains a challenge, this review forms a first step towards systematic research in the field and contributes to shaping directions for future research. Lay Description What is currently known about the subject matter? Mobile devices and applications are widely used by young children. Few studies examined their impact on learning and development. What their paper adds to this? This paper reviews studies reporting learning effects of mobile applications on children 2 to 5 years old. Learning gains are reported on literacy development, mathematics, science, problem‐solving, and self‐efficacy. Implications of study findings for practitioners Design features, adults, and similarity between contexts should be considered when mobile applications are used with young children. Mobile applications should be used with caution as there is yet a limited understanding of their impact on young children.